2017
DOI: 10.3389/fnins.2017.00179
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Does Not Affect Lower Extremity Muscle Strength Training in Healthy Individuals: A Triple-Blind, Sham-Controlled Study

Abstract: The present study investigated the effects of anodal transcranial direct current stimulation (tDCS) on lower extremity muscle strength training in 24 healthy participants. In this triple-blind, sham-controlled study, participants were randomly allocated to the anodal tDCS plus muscle strength training (anodal tDCS) group or sham tDCS plus muscle strength training (sham tDCS) group. Anodal tDCS (2 mA) was applied to the primary motor cortex of the lower extremity during muscle strength training of the knee exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…Studies assessed both men and women, with mean ± SD sample size per study was 14.4 ± 5.7 (from 6 to 24 participants) with a median of 12, aged from 17 to 42 years and different levels of physical activity/fitness (ranging from low active individuals to athletes). Regarding tDCS timing, 16 studies (72.7%) applied tDCS before exercise, three studies (13.6%) applied tDCS during exercise, one study (4.5%) applied tDCS both before and during exercise, one study (4.5%) applied tDCS over repeated sessions, and one (4.5%) during exercise training [58]. The effect of tDCS for improving exercise performance was assessed for muscle strength in 15 studies (68.2%), from which 10 (45.5%) used isometric, three (13.6%) used isokinetic, and two (9.1%) used dynamic strength exercise.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies assessed both men and women, with mean ± SD sample size per study was 14.4 ± 5.7 (from 6 to 24 participants) with a median of 12, aged from 17 to 42 years and different levels of physical activity/fitness (ranging from low active individuals to athletes). Regarding tDCS timing, 16 studies (72.7%) applied tDCS before exercise, three studies (13.6%) applied tDCS during exercise, one study (4.5%) applied tDCS both before and during exercise, one study (4.5%) applied tDCS over repeated sessions, and one (4.5%) during exercise training [58]. The effect of tDCS for improving exercise performance was assessed for muscle strength in 15 studies (68.2%), from which 10 (45.5%) used isometric, three (13.6%) used isokinetic, and two (9.1%) used dynamic strength exercise.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Furthermore, the use of tDCS outside the lab by the wider community may produce uncertain results due to inadequate electrode positioning, contact, impedance, and current flow. It should be noted that only two studies (9.1%) used tDCS for performance improvement over repeated sessions, with four [62] or seven sessions [58], and the safety for daily use of tDCS such as before/during training sessions is still to be evaluated. Therefore, the widespread application of tDCS outside the lab, such as with commercial devices, should be treated with significant caution until clear scientific evidence supports its safety and efficacy.…”
Section: Tdcs For Improving Muscle Strength In Isometric Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Lower extremity muscle strength modulation has also been assessed through tDCS application, although results are rather inconclusive. For example, some results showed tDCS to be effective in modulating isometric muscle strength [10,14,15], whereas other studies provide evidence to the contrary [16][17][18]. It is of note that, among others stimulation sites, current density (mA/cm 2 ), as well as strength training background of participants all differ between studies, making interpretations difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, several other studies showed the opposite results, reporting that tDCS may not significantly improve these functions. Maeda et al [37], for example, observed that anodal tDCS failed to enhance the lower extremity muscle strength in healthy participants. Similarly, studies also showed that anodal tDCS did not significantly elevate the maximal force production of knee extensors [38] nor enhance static balance ability [39].…”
Section: Discussionmentioning
confidence: 99%